2022
DOI: 10.1007/s10113-022-01986-0
|View full text |Cite
|
Sign up to set email alerts
|

Impacts and economic costs of climate change on Mexican agriculture

Abstract: This study quantifies the impacts of climate change on yields and the corresponding economic losses in six relevant crops that account for 65% of the harvested area in Mexico and are highly relevant in terms of consumption and economic value. The results show that crop yields could decrease considerably during this century, especially in the rainfed management system. Under a high-emission scenario, large reductions in yields are expected by the end of this century for both rainfed and irrigated management sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
(56 reference statements)
2
2
0
Order By: Relevance
“…It is shown that under the baseline scenario (SSP370), rainfed maize yields could decrease at least 40% for 11 states of the country and up to 60%-80% in some regions by the end of the century. These results are consistent with the range of yield reductions reported in Estrada et al (2022), which analyzes yield changes of the EPIC model under the RCP8.5 and RCP2.6 scenarios Frontiers in Environmental Science frontiersin.org for rainfed maize in Mexico. The probabilities of exceeding a userdefined risk threshold of −30% reduction in rainfed maize yields are estimated and the areas with higher risks are identified.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It is shown that under the baseline scenario (SSP370), rainfed maize yields could decrease at least 40% for 11 states of the country and up to 60%-80% in some regions by the end of the century. These results are consistent with the range of yield reductions reported in Estrada et al (2022), which analyzes yield changes of the EPIC model under the RCP8.5 and RCP2.6 scenarios Frontiers in Environmental Science frontiersin.org for rainfed maize in Mexico. The probabilities of exceeding a userdefined risk threshold of −30% reduction in rainfed maize yields are estimated and the areas with higher risks are identified.…”
Section: Discussionsupporting
confidence: 89%
“…Under an inaction scenario (SSP370) the present value of the losses in rainfed maize yields amounts to $130,000 million pesos, with much of these losses occurring in Chiapas, Jalisco, Veracruz, Oaxaca, and Guerrero. As expected, these losses are lower than those reported by Estrada et al (2022) for a higher emissions scenario (RCP8.5). However, these estimates are consistent with what could be expected for the SSP370, and a similar geographical distribution of losses is shown.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Climate change can impact honey bee colonies negatively and/or positively, but in tropical regions, climate change has the potential to reduce honey yields by almost half (Delgado et al., 2012 ). Climate change models predict that parts of Mexico will experience more frequent droughts and a rise in temperature in the future (Estrada et al., 2022 ). Lack of rainfall would reduce plant bloom and survival, which would negatively impact honey yields but also reduce colony buildup and reproduction (Frazier et al., 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…Global climate change has brought on serious ecological challenges [1][2][3], and researchers have mainly elaborated on the current problems from various aspects such as nature (plant growth [4,5], land desertification [6,7]), national economy [8,9], agriculture [10][11][12]), and society (policy guidelines [13,14], urban construction [15,16], human health [17][18][19][20]). To cope with climate change and alleviate the deterioration of the environment, China has incorporated the "dual-carbon" policy into the construction of ecological civilization and the "14th Five-Year Plan" [21,22] to respond to the transformation and upgradation of contemporary society.…”
Section: Introductionmentioning
confidence: 99%